The Effect of Playing Video Advertisement Inside a Car on Driver Visual Distraction - Abhari, Mohammadreza; Tabibi, Masoud; Moghadas Nejad, Fereydoon; Ramezani Khansari, Ehsan; Amini, Ehsan (Civil Engineering Journal, 2018)
With the development of in-car technologies and the use of portable devices such as tablets inside the car, one of the most interesting topics for different companies might be to promote advertising within the car. The most important issue with regard to advertising inside the vehicle is the safety issues and issues related to driver distraction. The NHTSA regulation, restricted in- car advertising in 2014, whereas, by increasing the use of in-vehicle devices and technologies, in 2016 showing video images in the vehicles were allowed under certain circumstances. The current research aims to assess the degree of visual distraction of driver caused by video advertisements broadcasted inside a car. The results of this study indicate that the type of advertisement has a direct impact on the visual distraction of the driver. In addition, findings indicate that in case of playing an advertisement in a simple form (accommodated by a speech), a safer situation might be expected compared to situations in which the same advertisement has been broadcasted by a musical content (with or without a speech).